Comparison of Fine Particulate Matter and Carbon Monoxide Exposure Concentrations for Selected Transportation Modes. Issue 1 (January 2014) - Jiao, Wan; Frey, H. Christopher
Daily commutes may contribute disproportionately to overall daily exposure to urban air pollutants such as particulate matter less than 2.5 Μm (PM2.5 ) and carbon monoxide (CO). PM2.5 and CO concentrations were measured and compared across pedestrian, bus, and car modes during lunchtime and the afternoon peak hour within a 3–week time period on preselected round-trip routes. Variability in the concentration ratios of PM2.5 and CO for the selected transportation modes was quantified, and factors affecting variability in concentrations were identified. Exposure concentrations of transportation modes were sensitive to mode and were affected by factors such as vehicle ventilation and proximity to on-road emission sources. In general, pedestrian and bus modes had higher PM2.5 concentrations than did the car mode. However, the car mode had the highest average CO concentrations among the selected modes. Near-road pedestrian PM2.5 concentrations generally covaried with fixed site monitor (FSM) measurements, but there was little correlation between pedestrian CO concentrations and FSM data. Field studies such as this one are needed to develop input data for simulation models of population-based exposure to predict more accurately exposure concentrations for transportation modes.